2008
DOI: 10.1089/apc.2007.0110
|View full text |Cite
|
Sign up to set email alerts
|

Family Experiences with Pediatric Antiretroviral Therapy: Responsibilities, Barriers, and Strategies for Remembering Medications

Abstract: This study examines the relationship between adherence to pediatric HIV regimens and three family experience factors: (1) regimen responsibility; (2) barriers to adherence; and (3) strategies for remembering to give medications. Caregivers of 127 children ages 2-15 years in the PACTS-HOPE multisite study were interviewed. Seventy-six percent of caregivers reported that their children were adherent (taking Ն 90% of prescribed doses within the prior 6 months). Most caregivers reported taking primary responsibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 64 publications
4
40
0
7
Order By: Relevance
“…Marhefka et al (2008) found that caregivers of children on anti-retroviral medications who reported more barriers to medication taking (e.g. forgetfulness, child refuses medications, too busy, change in routine) reported that their children were less adherent to their medication regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Marhefka et al (2008) found that caregivers of children on anti-retroviral medications who reported more barriers to medication taking (e.g. forgetfulness, child refuses medications, too busy, change in routine) reported that their children were less adherent to their medication regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Por várias razões, ao se atribuir a responsabilidade de administração da terapia antirretroviral às próprias crianças, sem a supervisão dos pais ou responsáveis, torna-se praticamente improvável que elas completem o esquema com sucesso (23,46). Assim, estimular o envolvimento do cuidador no tratamento, tentando compreender o que o impede de realizar a tarefa de administração dos medicamentos à criança e o que o ajuda a ter sucesso, pode ser crucial para o desenvolvimento de intervenções passíveis de promover uma adesão eficaz (46).…”
Section: Antecedentes Do Conceito Adesão Ao Tratamento De Crianças Sounclassified
“…Assim, estimular o envolvimento do cuidador no tratamento, tentando compreender o que o impede de realizar a tarefa de administração dos medicamentos à criança e o que o ajuda a ter sucesso, pode ser crucial para o desenvolvimento de intervenções passíveis de promover uma adesão eficaz (46).…”
Section: Antecedentes Do Conceito Adesão Ao Tratamento De Crianças Sounclassified
“…Children with chronic illnesses such as asthma, human immunodeficiency virus, inflammatory bowel disease, and organ transplantation, as well as their parents, have reported various barriers to medication adherence [12][13][14][15][16][17][18][19]. The most common barriers identified across pediatric chronic illnesses include cognitive factors (forgetting, difficulty with the complex regimen, time management) and life-style adaptation (being away from home, interference with an activity, changes in routine) [12][13][14][15][16][17][18][19].…”
Section: Perceived Barriersmentioning
confidence: 99%
“…The most common barriers identified across pediatric chronic illnesses include cognitive factors (forgetting, difficulty with the complex regimen, time management) and life-style adaptation (being away from home, interference with an activity, changes in routine) [12][13][14][15][16][17][18][19]. Additionally, psychological factors (lack of self-efficacy, denial, distrust, behavioral defiance), social factors (lack of social support, peer pressures), and family issues (conflict between parents and children) also play a major role in poor adherence [13][14][15]. Although barriers related to the disease and the prescribed medications (difficulty swallowing pills, disliking the taste) have been studied, they are not as commonly cited as barriers for nonadherence [13,15].…”
Section: Perceived Barriersmentioning
confidence: 99%